Aberrant Activation of NF-κB Signalling in Aggressive Lymphoid Malignancies - Ruth Kennedy; Ulf Klein (Cells, 2018)
Lymphoid malignancies frequently harbor genetic mutations leading to aberrant activation of nuclear factor-κB (NF-κB) signaling; in normal cells, this pathway has important roles in the control of cell growth, survival, stress responses, and inflammation. Malignancies with mutations in NF-κB pathway components can derive from all cell stages of mature B-cell development; however, aberrant NF-κB activity is particularly prevalent in aggressive subtypes of non-Hodgkin lymphoma and myeloma. NF-κB activation is mediated by two separate pathways, the canonical and alternative pathway, and five downstream transcription factor subunits. Recent findings implicate a predominant role for distinct NF-κB pathways and subunits in certain lymphoma subtypes and myeloma; findings which are complemented by the realization that individual NF-κB subunits can have unique, non-redundant biological roles in the putative tumor precursor cells, including activated B cells, germinal center B cells and plasma cells. The knowledge gained from these studies may be exploited for the development of therapeutic strategies to inhibit aberrant NF-κB activity at the level of the transcription-factor subunits and their target genes, as global inhibition of the pathway is toxic. Here, we provide an overview on the role of aberrant NF-κB activation in aggressive lymphoid malignancies and discuss the potential importance of individual NF-κB subunits in the pathogenesis of tumor subtypes.